L’homosexualité, une « question difficile ». Distinction et hiérarchisation des sexualités dans l’éducation sexuelle en milieu scolaire - Aurore Le Mat (Genre, Sexualité et Société)
Sex education has been compulsory in the French school system since 2001. What kind of content is proposed to the pupils and to the sex educators ? This paper analyzes the processes of classification and hierarchical organization of homosexuality and heterosexuality in sex education curricula. There are different kinds of “invisible barriers” (Varikas, 2007) that relegate homosexuals to the status of sexual outcast. At least three points are made to keep homosexuality in this particular place : it is a personal question, it is a matter of specific practices, it is a matter of age (and does not concern children or teenagers). The distinctions between public and private, between the universal and the specific, and between adolescence and adulthood are three kinds of “invisible barriers” that set up an implicit hierarchy of heterosexuality over homosexuality. A fourth kind of barrier appears among the very few representations of homosexuality in the French educational material: lesbians are invisible and remain the ultimate sexual outcast.